2017
DOI: 10.7150/jca.20971
|View full text |Cite
|
Sign up to set email alerts
|

Post-Resection Exhaustion of Intra-Platelet Serotonin: Also an Indicator of Early Hepatocellular Carcinoma Recurrence?

Abstract: Purpose: Serotonin (5-hydroxytryptamine, 5-HT) is well known for its growth stimulatory effect on several types of carcinoma and tumor cells. Since a large portion of 5-HT is stored and transported by platelets, the aim of this study was to assess the influence of platelet-sequestered 5-HT on post-resection hepatocellular carcinoma (HCC) recurrence.Methods: This pilot study was conducted in a cohort of forty patients diagnosed with HCC undergoing partial hepatectomy. 5-HT levels in serum, plasma and intra-plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…In patients who underwent hepatic resection, the presence of a lower level caused a 0.67-fold increase in the risk of overall mortality and a 0.44-fold increase in the risk of disease-free death in comparison with a higher level [ 28 ]. In our previous study, we also observed the postresection depletion of platelet count in patients who developed early HCC recurrence [ 29 ].…”
Section: Influence Of Platelet Countmentioning
confidence: 91%
See 1 more Smart Citation
“…In patients who underwent hepatic resection, the presence of a lower level caused a 0.67-fold increase in the risk of overall mortality and a 0.44-fold increase in the risk of disease-free death in comparison with a higher level [ 28 ]. In our previous study, we also observed the postresection depletion of platelet count in patients who developed early HCC recurrence [ 29 ].…”
Section: Influence Of Platelet Countmentioning
confidence: 91%
“…Deb et al observed depleted IP serotonin in patients with cervical cancer and found that platelets from cancer patients released more serotonin on thrombin stimulation than the control group [ 46 ]. In a homogenous prospective cohort of patients with HCC, we found a postresection exhaustion of IP serotonin was able to predict early HCC recurrence [ 29 ]. The study conducted by Padickakudy et al, with a highly standardized preparation of platelet, and our study, however, referred to different postresection time points; the former study monitored IP serotonin during early postoperative period whereas we measured it after 4 weeks of liver resection.…”
Section: Intraplatelet Serotonin: Wrapped In An Enigma?mentioning
confidence: 99%
“…Platelet-stored PDGF-BB is easily available for the tumor and surrounding stroma[14]; thus sPDGF-BB reflects the magnitude of proangiogenic influence related to the growth factor. Platelet dysfunction is already a known phenomenon in cancer progression; platelets hyperactivity and platelet exhaustion are frequently seen in cancer patients[1720]. We previously observed exhaustion of IP serotonin in patients with early cancer recurrence[17]; likewise, we speculated that the depleted sPDGF-BB might attribute to the platelet exhaustion; however, we observed a weak trend with total platelet (IP) PDGF-BB.…”
Section: Discussionmentioning
confidence: 54%
“…Concerning the pro-angiogenic effect, the mutual influence of platelets and tumor cells also is not fully determined. A recent study performed on twenty-four women with active breast cancer and ten healthy controls showed that breast cancer and its chemotherapeutic treatment influence platelet phenotype, by increasing VEGF release and modulating the response to antiplatelet therapy [119]. Noticeably, an autocrine-paracrine loop, occurring in the bone marrow microenvironment and involving VEGFR-1-dependent megakaryocyte maturation has been documented [120].…”
Section: Platelet-derived Bioactive Compoundsmentioning
confidence: 99%